A participation model based on community forum as a reproductive health knowledge transaction space to increase male participation in vasectomy - Noverman Duadji; Novita Tresiana (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The first background of this research is the low participation of male vasectomy KB due to lack of information and low male contraceptive services. The second background of this research is Friedmann’s (2011) idea of citizen forum as transaction space which becomes communication media in the form of equal dialogue.This study aims to analyse the causes of low participation in the vasectomy method of family planning (KB) in South Lampung Regency; analyse the grassroots organisations in the community as the support system for a potential increase in the society’s participation in vasectomy as a part of family planning (KB); and develop a model of vasectomy to increase the participation in South Lampung Regency. This study utilised primary and secondary data which were collected and analysed using qualitative-descriptive method. The research was conducted in nine villages in South Lampung Regency. The findings showed that the major failure for participation in the vasectomy method of family planning (KB) was caused by a lack of a representative knowledge transaction space in family planning (KB) and reproductive health. On the other hand, the existing active societal-institutional support system can be utilised as the space for knowledge transaction. A solution to enhance a social participation model through community forums is urgently needed.